Penguatan Fungsi dan Peran Pengawasan oleh Anggota Badan Permusyawaratan Desa (BPD) di Kecamatan Jatiwangi Majalengka - Sholihah, Lilis; Sinaga, Jona Bungaran Basuki; Rifa’i, Muhamad; Ginting, Arwanto Harimas (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
The Village Consultative Body, as a community representative institution, has an important role and strategic function in fighting for public interests. This is done through supervision of the village government as well as providing input and criticism to produce quality village policies, encourage equitable development, and ensure effective government management. However, in carrying out supervision, some BPD members do not fully understand the mechanisms and techniques for implementing supervision through social accountability. The aim of this activity is to provide knowledge about the duties and functions of BPD as well as the concept of social accountability associated with these duties and functions. The location of the activity is in Jatiwangi District, Majalengka Regency. The activity was carried out by presenting the duties and functions of BPD based on theoretical, normative and empirical reviews by the PkM Lecturer Team and Praja Pratama. Next, there was a discussion and question and answer session between the PkM Lecturer Team and the audience. It can be concluded that the BPD has carried out its functions and duties, such as exploring, collecting and channeling community aspirations, holding deliberations, monitoring the performance of the village head and collaborating with the village government. However, it is not yet optimal in terms of structured administration and bookkeeping. This has the impact of not conveying findings of abuse of authority to higher government authorities. The BPD in Jatiwangi District should begin to administer and record their activities, either through formal instruments in accordance with applicable regulations, or through informal records and collaborating in the administration of village government.